The European Green Deal: greenwashing compounded by deregulation (Omnibus law) or a genuine paradigm shift? - Nicolas de Sadeleer (European Journal of Risk Regulation)
The green transition promoted by the European Green Deal (EGD) is not simply a matter of achieving climate neutrality by 2050. This macro-objective enshrined in European Climate Law (ECL) is complemented by the objectives of zero pollution and ecological resilience. These three intertwined objectives further manifest themselves in a myriad of sub-objectives, which are to be achieved through an array of interconnected regulatory and financial measures falling with the scope of energy, industrial, transport, external trade, agricultural and environmental policies. The genius of the EGD reform lies precisely in the fact that it articulates a number of complementary objectives whilst also operating within the framework of several EU policies. The aim of this article is to assess whether the 160 legislative instruments implementing the EGD amount to greenwashing of EU economic policies or whether they are in actual fact testament to a paradigm shift. This issue is all the more topical now that several simplification proposals have been proposed by the European Commission.